Assessment of Pattern of Rainfall in Kerala and its Forecasting using NNAR Model - Gleeja V.L.; Rini George (Journal of the Indian Society of Agricultural Statistics, 2025)
The economy of the state Kerala is dominated by agriculture and the agriculture depends on rainfall. Hence, the study of rainfall is important and its forecasting will aid in crop and hydrological planning. The present study analyzed the pattern of rainfall in Kerala for the period 1991 to 2020 and obtained annual average rainfall as 2906.79 mm. There was no significant trend in annual rainfall. As per monthly rainfall data, month of June receives highest rainfall followed by July. Monthly rainfall had been modelled using Seasonal Autoregressive Moving Average model (SARIMA) and Neural Network Auto Regression (NNAR) model. Comparison of models based on the accuracy measures, revealed NNAR (6,1,4)[12] as the best model for forecasting rainfall in Kerala. Monthly rainfall for 2021 and 2022 was predicted and it showed that rainfall will be high in the month of July.